Aplikasi Edible Coating Gel Lidah Buaya (Aloe vera L.) untuk Mempertahankan Jambu Biji Varietas Getas Merah (Psidium guajava L.) Selama Masa Simpan - Armando Beresman Pangaribuan; Maria Marina Herawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the effect of Aloe vera Gel edible coating concentration on the quality of getas merah guava during storage and to identify the optimal concentration for maintaining fruit quality. The method used in this study was a Completely Randomized Block Design (CRBD) with five treatment concentrations of Aloe vera Gel edible coating: K1 (control), K2 (20%), K3 (25%), K4 (30%), and K5 (35%). The measured parameters included fruit moisture content, respiration rate, weight loss, firmness, reducing sugar, and vitamin C content. Measurements were conducted on days 0, 3, 6, 9, and 12 of storage. The results showed that the concentration of Aloe vera Gel edible coating significantly affected fruit moisture content, respiration rate, firmness, reducing sugar, and vitamin C levels in getas merah guava. However, there was no significant effect on fruit weight loss. The 35% Aloe vera Gel edible coating concentration (K5) was the most effective treatment in maintaining the quality of getas merah guava during storage. Keywords: Edible coating, Aloe vera Gel, Getas merah guava.